MUMFORD, Stephen & TUGBY, Matthew (eds.): Metaphysics and Science, Oxford, Oxford University Press, 2013. - Triviño Alonso, Vanessa (Daimon Revista Internacional de Filosofia, 2014)
Reseña de este libro.